FILSAFAT SEBAGAI DASAR PERKEMBANGAN ILMU PENGETAHUAN - Khairul Muzakir; Cut Noer Aqlima; Toharuddin Simbolon; Khairil Agusrian; Rosita Dongoran (JURNAL ILMIAH NUSANTARA, 2024)
This research aims to examine the role of philosophy as the basis for the development of science. The key questions to be answered involve how philosophy provides the basis for the formation of scientific concepts and theories, how philosophy provides the basis for the development of scientific methods, and how philosophy guides scientists in conducting research. This research uses library research method, which is a method of collecting data through reading and reviewing books and literature related to the research theme. In conclusion, it can be recognized that the philosophy of science is not only a theoretical mirror of science, but also a driving force in shaping and directing the evolution of science.